A Nanofiber Sheet Incorporating Vitamin B12 Promotes Nerve Regeneration in a Rat Neurorrhaphy Model. Issue 12 (December 2019) - Miyamura, Satoshi; Iwahashi, Toru; Sayanagi, Junichi; Hirai, Yukio; Okada, Kiyoshi; Oka, Kunihiro; Niiyama, Eri; Uto, Koichiro; Ebara, Mitsuhiro; Yoshikawa, Hideki; Murase, Tsuyoshi; Tanaka, Hiroyuki
Abstract : Background: Outcomes of peripheral nerve repair after injury are often suboptimal. Therefore, developing biological approaches to augment nerve regeneration is important. In this in vivo study, we tested the hypothesis that augmentation with an electrospun nanofiber sheet incorporating methylcobalamin (MeCbl) would be effective for regeneration after peripheral nerve transection and repair. Methods: Rats were divided into 3 groups that either underwent sciatic nerve repair with or without the MeCbl sheet, or a sham operation. At 4 and/or 8 weeks after the operation, sensory and motor functional recovery, along with histological findings, were compared among the groups using the toe-spreading test, mechanical and thermal algesimetry tests, tibialis anterior muscle weight measurements, electrophysiological analyses, which included nerve conduction velocity (NCV), compound muscle action potential (CMAP), and terminal latency (TL), and histological analyses involving the myelinated axon ratio, axon diameter, and total axon number. Results: Compared with the repair group without the MeCbl sheet, the repair group with the MeCbl sheet showed significant recovery in terms of tibialis anterior muscle weight, NCV and CMAP, and also tended to improve in the toe-spreading test, mechanical and thermal algesimetry tests, and TL. Histological analyses also demonstrated that the myelinated axon ratios and axon diameters were significantly higher. Among these findings, the repair group with the MeCbl sheet demonstrated the same recovery in NCV as the sham group. Conclusion: This study demonstrated that electrospun nanofiber MeCbl sheets promoted nerve regeneration and functional recovery, indicating that this treatment strategy may be viable for human peripheral nerve injuries.